2016
DOI: 10.1210/jc.2016-2371
|View full text |Cite
|
Sign up to set email alerts
|

High Sclerostin and Dickkopf-1 (DKK-1) Serum Levels in Children and Adolescents With Type 1 Diabetes Mellitus

Abstract: Our study highlighted (1) the high serum levels of DKK-1 and sclerostin in T1DM children and their relationship with altered glycemic control and (2) the effect of CSII on improvement of glycemic control and bone health in T1DM children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 33 publications
6
55
1
Order By: Relevance
“…Although the biological roles of sclerostin and corresponding benefits of antisclerostin antibodies have been illuminated, much epidemiological data regarding serum sclerostin levels is still unclear. Most researches about sclerostin levels are focused on special groups, and there are few studies on general healthy people from communities (He et al, 2014;Faienza et al, 2017;Hansen et al, 2019;Pekkolay et al, 2019;Singh et al, 2019;Yang et al, 2019). The associations of serum sclerostin to bone metabolism markers in different population show inconsistent results, and only a few studies have been conducted to investigate relations of serum slcerostin to sex hormones (Garnero et al, 2013;Szulc et al, 2013;Yamamoto et al, 2013;Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the biological roles of sclerostin and corresponding benefits of antisclerostin antibodies have been illuminated, much epidemiological data regarding serum sclerostin levels is still unclear. Most researches about sclerostin levels are focused on special groups, and there are few studies on general healthy people from communities (He et al, 2014;Faienza et al, 2017;Hansen et al, 2019;Pekkolay et al, 2019;Singh et al, 2019;Yang et al, 2019). The associations of serum sclerostin to bone metabolism markers in different population show inconsistent results, and only a few studies have been conducted to investigate relations of serum slcerostin to sex hormones (Garnero et al, 2013;Szulc et al, 2013;Yamamoto et al, 2013;Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study of 106 T1DM subjects (12.2 ± 4 years), along with 80 controls, serum sclerostin and dickkopf-1 (DKK-1; another inhibitor of the Wnt/beta-catenin pathway) significantly increased (69). However, these findings were not confirmed in another cross-sectional study of 40 T1DM children (age 13.04 ± 3.53 yr) and 40 controls (70).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified that the deficiency of vitamin D is strongly connected with diabetes mellitus type 1 45,46 and that the death of islet cells and its complements can be easily avoided by the vitamin D, which in turn, will promote the production of insulin. 47,48 Hence, beta cells can be negatively implicated by the lower level of 25(OH)D3.…”
Section: Discussionmentioning
confidence: 99%